FDI and Trade : Exemplification of Poland and other Post-communist States - Katarzyna Zukrowska; Malgorzata Gracik; Anna Pochylczuk; Dominik Sobczak; Jolanta Zombirt (Free University Berlin, Jean Monnet Centre of Excellence, 2002)
Study is focused on mutual relations between FDI and foreign trade in economies going through systemic transformation after 1989. Its aim is to indicate: (1) how big were the streams of FDI inflows and outflows; (2) what were the institutional arrangements for liberalization of FDI and trade; (3) what type of impact had FDI flows on foreign trade: was it stimulated and if so, in what direction (imports or exports); (4) who were the main investors (states engaged in capital exports) and branches most attractive for investors. The study is illustrating a new approach to international economic relations in which assumption that production factors are not transferable internationally on large scale and thus stimulating foreign trade is replaced by an assumption that production factors are transferable and thus stimulating trade and in consequence wealth. They also increase interdependence within the process of integration on regional scale and globalization on worldwide scale. Study is aimed at showing scale of flows and their role in restructuring and deregulating the economies in transformation, bringing them at the same time closer to newly formulated division of labor in which globalization is a process seen as integration on a wider scale than during previous years within the divided world.
Keywords: F15; F02; 330; Eastern Enlargement of the EU; Trade; FDI; EU-Erweiterung; Aussenwirtschaft; Direktinvestition; EU-Staaten; Polen; Tschechische Republik; Estland; Ungarn; Slowakei